Diversity of methanogens in the hindgut of grower and finisher pigs - Zhen Cao; Xin Di Liao; Juan Boo Liang; Yin Bao Wu; Bin Yu (African Journal of Pig Farming, 2019)
This study examined the diversity of the methanogens in the hindgut of two different weight groups of pigs and correlated it with the amount of digested organic carbon (OC) and various components of dietary fiber. Five grower (58.9 ± 1.15 kg) and five finisher (89.4 ± 0.85 kg) Duroc × Landrace × Large Yorkshire female pigs were allocated into two groups and individually housed in cages. During the experiment, feed intake and fecal output were recorded for determination of apparent digestibility of OC, crude fiber (CF), neutral detergent fiber (NDF) and acid detergent fiber (ADF). At the end of the digestibility trial, pigs were sacrificed, and the contents of five segments of hindgut were sterilely collected to determine diversity of methanogens. Total microbial DNA of the hindgut contents was used as template for amplification of the methanogen16S rRNA gene, and the PCR products were further subjected to denaturing gradient gel electrophoresis (DGGE) analysis. Results show that the number of DGGE bands and Shannon diversity index for the 90 kg pigs were higher (P<0.05) than those for the 60 kg pigs. Methanogen communities did not alter along the different segments of the hindgut for the two weight groups. In addition, the amount of OC, CF, NDF and ADF digested (g/d) for the 90 kg pigs (1018.77, 23.11, 268.86 and 99.16, respectively) was higher (P<0.05) than the respective values for the 60 kg pigs (669.27, 13.77, 222.31 and 69.07), indicating that the higher diversity of methanogens in the former group was related to the higher quantity of fiber materials fermented in the hindgut. The positive correlation (p<0.05) between number of DGGE bands and Shannon diversity index with quantity of digested OC and ADF further reaffirmed the above suggestion.